Earphone in urinary bladder- A rare entity for sexual gratification (Indian Journal of Case Reports, 2019)
The incidence of foreign body insertion in urethra was rare, but there has been a gradual increment in such cases nowadays.. The most common cause is to get sexual gratification. The management of these cases is individualized according to size, type, and location. Here we present a unique case report of earphone in the urinary bladder. A 17-year old male was admitted to the hospital with earphone inserted in his urinary bladder. The boy was operated for the removal of the broken end of the earphone. Such cases are common and needs proper attention and care which should be coupled with psychiatric consultation.